COMMODITY INVESTMENT MODEL AND ITS SIGNIFICANCE FOR INVESTORS - Novotný, Josef (European Scientific Journal, ESJ, 2015)
There are often changes in today’s market environment, which force investors and companies to seek new solutions, practices, support new branches, and design new models etc. This article discusses a commodity investment model and its importance for investors. It aims to determine the right price for commodities based on the designed investment model. The main problem with commodities in the investment environment is that it is very difficult to determine intrinsic value, as is required for equities. The result of this paper is a model and its mathematical expression, which determines the right price, including its application to selected commodities. The model will facilitate the decision-making of investors on commodity markets when to buy and when to sell selected commodities. The use of this model in practice can provide investors a competitive advantage on the commodity market.